Multiple paths to the same destination: Influence of gene flow on convergent evolution. Issue 9 (23rd April 2021) - Yamasaki, Yo Y.; Kitano, Jun
Abstract : Elucidation of the genetic mechanisms of convergent evolution, the evolution of similar or the same phenotypes in phylogenetically independent lineages, helps predict how populations will respond to the same selective pressures. Convergent evolution can be caused by either the fixation of identical‐by‐descent alleles, independent mutations at the same gene, or mutations in different genes controlling the same trait. To what extent does the fixation of identical‐by‐descent alleles lead to convergent evolution in isolated populations where inflow of adaptive alleles from other populations is limited? In a From the Cover article in this issue of Molecular Ecology,  Kemppainen et al. (2021) compared the genetic basis for the reduction of pelvic structures in three isolated freshwater populations of nine‐spined stickleback ( Pungitius pungitius ) from Northern Europe. The authors used quantitative trait loci (QTL) mapping to reveal that the pelvic reduction in these three populations was caused by mutations at different genetic loci. In contrast to studies in three‐spined stickleback ( Gasterosteus aculeatus ), where independently derived Pitx1 mutations were shown to be responsible for plate reduction across multiple freshwater populations, Kemppainen et al. (2021) found Pitx1 to be the candidate causative gene for only one population of P .  pungitius . This study highlights the importance of genetic studies of convergent evolution, not only in the presence of gene flow but also in its absence for a better understanding of the genetic architecture of convergent evolution.